2008
DOI: 10.3171/ped-08/01/057
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of spinal deformity after resection of intramedullary spinal cord tumors in children who underwent laminectomy compared with laminoplasty

Abstract: Object Gross-total resection of pediatric intramedullary spinal cord tumor (IMSCT) can be achieved in the majority of cases while preserving long-term neurological function. Nevertheless, postoperative progressive spinal deformity often complicates functional outcome years after surgery. The authors set out to determine whether laminoplasty in comparison with laminectomy has reduced the incidence of subsequent spinal deformity requiring fusion after IMSCT resection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
91
2
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(104 citation statements)
references
References 33 publications
0
91
2
11
Order By: Relevance
“…11) In addition to the growth of spine, these features accentuate the alteration of spinal biomechanics caused by tumor resection with consequent spinal deformity. 11,34,44) The length and extent of laminectomy, which leads to loss of posterior supporting elements, are directly associated with increased risk of postoperative deformity, 18,23,28,46) although other factors such as age, tumor location, preoperative spinal deformity, extent of facet resection, and degree of tumor resection also influence the occurrence of postoperative spinal deformity. 30,44) In consideration of the hypothesis above, osteoplastic laminotomy, which enables replacement of the original bony structure, may be associated with less spinal deformity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11) In addition to the growth of spine, these features accentuate the alteration of spinal biomechanics caused by tumor resection with consequent spinal deformity. 11,34,44) The length and extent of laminectomy, which leads to loss of posterior supporting elements, are directly associated with increased risk of postoperative deformity, 18,23,28,46) although other factors such as age, tumor location, preoperative spinal deformity, extent of facet resection, and degree of tumor resection also influence the occurrence of postoperative spinal deformity. 30,44) In consideration of the hypothesis above, osteoplastic laminotomy, which enables replacement of the original bony structure, may be associated with less spinal deformity.…”
Section: Discussionmentioning
confidence: 99%
“…30) Decreased incidence of progressive spinal deformity requiring fusion was demonstrated following osteoplastic laminotomy for the resection of intramedullary spinal cord tumors in children. 23) Our patient was 3 months old when the surgery was performed. CT showed synchondroses at the center of each lamina which usually unites in the second or third year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 It has been showed that the laminoplasty when compared with the laminectomy decreases the postoperative spinal deformity for treatment of intradural lesions, especially at the thoracolumbar junction, in pediatric cases. 4 In the presented case we preferred to perform laminectomy and extensive duraplasty to ensure the effective decompression of the spinal cord. In the presented case rapid neurologic improvement was achieved immediately after operation and postoperative MRI showed no spinal deformity.…”
Section: Discussionmentioning
confidence: 99%
“…Whenever possible, a laminoplasty is preferred over a laminectomy as long as the tumor resection would not be compromised, because laminoplasty makes the revision operation substantially easier and safer. 24,27,31 If a laminectomy is necessary, one can replace the lamina and hold it in place with the miniplates used by hand surgeons. If that is not possible, closing the first layer of the soft tissues with a running, nonabsorbable, colored suture and closing the subsequent layer with an absorbable or noncolored suture will enable the surgeon to identify the last layer before the dura in the revision operation.…”
Section: Surgical Planning Patients With Cervical Deformity Diagnosedmentioning
confidence: 99%